Mapeamento das projeções retinianas para o sistema óptico acessório, colículo superior e complexo pré-tectal do sagui (callithrix jacchus) - Borda, Janaina Siqueira (2015)
The accessory optical system, the pretectal complex, and superior colliculus are important control centers in a variety of eye movement, being extremely necessary for image formation, consequently to visual perception. The accessory optical system is constituted by the nuclei: dorsal terminal nucleus, lateral terminal nucleus, medial terminal nucleus and interstitial nucleus of the posterior superior fasciculus. From a functional point of view they contribute to the image stabilization, participating in the visuomotor activity where all system cells respond to slow eye movements and visual stimuli, which is important for the proper functioning of other visual systems. The pretectal complex comprises a group of nuclei situated in mesodiencephalic transition, they are: anterior pretectal nucleus, posterior pretectal nucleus, medial pretectal nucleus, olivary pretectal nucleus and the nucleus of the optic tract, all retinal projection recipients and functionally are related to the route of the pupillary light reflex and the optokinetic nystagmus. The superior colliculus is an important subcortical visual station formed by layers and has an important functional role in the control of eye movements and head in response to multisensory stimuli. Our aim was to make a mapping of retinal projections that focus on accessory optical system, the nuclei of pretectal complex and the superior colliculus, searching mainly for pretectal complex, better delineation of these structures through the anterograde tracing with the B subunit of cholera toxin (CTb) followed by immunohistochemistry and characterized (measured diameter) synaptic buttons present on the fibers / terminals of the nucleus complex pré-tectal. In our results accessory optical system, including a region which appears to be medial terminal nucleus and superior colliculus, were strongly marked by fibers / terminals immunoreactive CTb as well as pretectal complex in the nucleus: optic tract, olivary pretectal nucleus, anterior pretectal nucleus and posterior pretectal nucleus. According to the characterization of the buttons it was possible to make a better definition of these nucleus.